Design, synthesis, and in vitro evaluation of BP-1-102 analogs with modified hydrophobic fragments for STAT3 inhibition. (1st January 2021) - Oleksak, Patrik; Psotka, Miroslav; Vancurova, Marketa; Sapega, Olena; Bieblova, Jana; Reinis, Milan; Rysanek, David; Mikyskova, Romana; Chalupova, Katarina; Malinak, David; Svobodova, Jana; Andrys, Rudolf; et al.
Abstract: Twelve novel analogs of STAT3 inhibitor BP-1-102 were designed and synthesised with the aim to modify hydrophobic fragments of the molecules that are important for interaction with the STAT3 SH2 domain. The cytotoxic activity of the reference and novel compounds was evaluated using several human and two mouse cancer cell lines. BP-1-102 and its two analogs emerged as effective cytotoxic agents and were further tested in additional six human and two murine cancer cell lines, in all of which they manifested the cytotoxic effect in a micromolar range. Reference compound S3I-201.1066 was found ineffective in all tested cell lines, in contrast to formerly published data. The ability of selected BP-1-102 analogs to induce apoptosis and inhibition of STAT3 receptor-mediated phosphorylation was confirmed. The structure–activity relationship confirmed a demand for two hydrophobic substituents, i.e. the pentafluorophenyl moiety and another spatially bulky moiety, for effective cytotoxic activity and STAT3 inhibition.